A chemisorption power generation cycle with multi-stage expansion driven by low grade heat. (15th October 2017) - Bao, Huashan; Ma, Zhiwei; Roskilly, Anthony Paul
Highlights: A multiple expansion resorption power generation cycle was proposed. Performance of the proposed cycle was studied at non-equilibrium condition. Sodium bromide – manganese chloride pair has the highest average work output. The cycle efficiency can achieve 0.06–0.15 with the temperature of 80–150 °C. Abstract: Ammonia-based chemisorption cycle driven by low grade heat exhibits vast potential for power generation because there exists huge pressure difference between the two salt-adsorbent-filled reactors. However, the intrinsic feature of ammonia as a wet fluid and the difficult match between chemisorption cycle and expansion device impede the development of such a power generation system and also increase the difficulty of practical implementation. To explore maximum benefits of this technology, the present work has proposed and studied a new resorption power generation cycle that applies multiple expansion. The application of multiple expansion integrated with reheating processes aims to overcome the limitation of the ammonia being wet fluid and fully harness the huge pressure difference that chemisorption can offer for power generation, leading to the improvement of energy efficiency. The performance of the proposed multiple expansion resorption power generation cycle using three typical resorption salt pairs, including sodium bromide – manganese chloride, strontium chloride – manganese chloride and sodium bromide – strontium chloride, have been investigated not just based on theoretical thermodynamics but also with the consideration of practical factors to obtain better understanding and more insights for a real system design. The multiple expansion resorption power generation using sodium bromide – manganese chloride and sodium bromide – strontium chloride pairs can achieve 100–600 kJ/kg (ammonia) work output when heat source temperature is from 30 °C to 150 °C; the multiple expansion using strontium chloride – manganese chloride pair has higher average work output per one expansion stage than that using the other two pairs. The cyclic energy efficiency can be achieved as 0.06–0.15 when implementing 2–4 expansions in a more practical scenario where the equilibrium pressure drop is set to 2 bar and the heat source temperature is in the range of 80–150 °C. Such efficiencies are circa 27–62% of Carnot efficiency under the same thermal conditions.